ANALISIS EFEKTIVITAS PENGGUNAAN ANGGARAN SEBAGAI ALAT PENGENDALIAN BELANJA LANGSUNG PADA BIRO HUKUM PROVINSI SULAWESI UTARA - Bumulo, Rahmawaty M.; Lambey, Linda; Mawikere, Lidia M. (Universitas Sam Ratulangi, 2018)
Budget has an important role any organization both government and private organizations. Budget is a guideline for the actions that will be implemented by the government. It includes the transfers of expenditure and financing plans that measured in Rupiah. Those are arranged systematically in accordance to a certain classification over one period. Budget preparation should be planned in advance so that the programs and activities targeted by the organization can be achieved. This study was conducted with the aim to find out how the budget is made, how the effectiveness of budget use is as a means of controlling direct expenditure, what factors influence the budget absorption mismatch in the North Sulawesi Provincial Legal Bureau in 2015-2017.The analytical method used is descriptive analysis. The results of the research for budget preparation are in accordance with the applicable regulations, that the effectiveness level from the year 2015 to 2017 as a whole is in the effective category. By the year of 2015 the effectiveness of the direct expenditure budget utilization is at 96.33% (effective), which has the lowest budget absorption compared to the year 2016-2017. By the year of 2016 the effectiveness of the direct budget utilization is at 99.76% (effective), and by the year2017 the level of effectiveness is 99.70% (effective). Budget absorption mismatches occur because of budget savings the residual value of spending, the difference in market prices from the prices already budgeted by the Sulawesi Provincial Legal Bureau.Keywords: Budgets, Effectiveness, Direct Expenditure